2010
DOI: 10.1056/nejmoa1003114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sibutramine on Cardiovascular Outcomes in Overweight and Obese Subjects

Abstract: Background The long-term effects of sibutramine treatment on the rates of cardiovascular events and cardiovascular death among subjects at high cardiovascular risk have not been established. Methods We enrolled in our study 10,744 overweight or obese subjects, 55 years of age or older, with preexisting cardiovascular disease, type 2 diabetes mellitus, or both to assess the cardiovascular consequences of weight management with and without sibutramine in subjects at high risk for cardiovascular events. All the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
492
1
29

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 817 publications
(536 citation statements)
references
References 30 publications
4
492
1
29
Order By: Relevance
“…showed a significantly higher risk of a primary CV outcome event in the sibutramine group than in the placebo group 59 . However, greater weight loss was associated with reduced overall CV risk in both groups 60 .Sibutramine was withdrawn from the market due to an uncertain benefit-risk balance, even in patients with T2DM.…”
Section: Sibutraminementioning
confidence: 90%
“…showed a significantly higher risk of a primary CV outcome event in the sibutramine group than in the placebo group 59 . However, greater weight loss was associated with reduced overall CV risk in both groups 60 .Sibutramine was withdrawn from the market due to an uncertain benefit-risk balance, even in patients with T2DM.…”
Section: Sibutraminementioning
confidence: 90%
“…This mechanism may cause prolongation of the QT interval. Unfortunately, the effect of sibutramine on the QT interval was not evaluated in the SCOUT study 3. Nevertheless, the findings in the cases of cardiac arrest associated with sibutramine suggest that this agent should be avoided in patients already taking medications that potentially prolong the QT interval.…”
Section: Discussionmentioning
confidence: 99%
“…The Sibutramine Cardiovascular and Diabetes Outcome Study (SCOUT) showed that treatment with sibtramine for 5 years in subjects with pre‐existing cardiovascular diseases significantly increased non‐fatal myocardial infarction and non‐fatal stroke, although the number of cardiovascular deaths or all‐cause mortality was not increased 3. Because the benefits of sibutramine do not outweigh the risk of the cardiovascular events, it has been withdrawn by the USA and European Union.…”
Section: Introductionmentioning
confidence: 99%
“…17 After physicians prescribed the drug for longer than a decade, the 2010 Sibutramine Cardiovascular Outcomes Trial (SCOUT), a randomized cardiovascular outcomes study in patients with cardiovascular disease, diabetes mellitus (DM), or both, found that sibutramine caused a greater rate of cardiovascular events. 18 In post hoc analysis by an FDA regulator, changes in BP did not predict these events, leaving the possibility of an unidentified mechanism of harm. 19 Some felt this signal for harm in high-risk patients should not be generalized to lowerrisk patients, who might lose weight without an increase in cardiovascular risk.…”
Section: The Checkered History Of Obesity Pharmacotherapymentioning
confidence: 99%
“…19 Some felt this signal for harm in high-risk patients should not be generalized to lowerrisk patients, who might lose weight without an increase in cardiovascular risk. 18 Others felt that patients with subclinical cardiovascular disease would be difficult to identify. 15 Ultimately, sibutramine was voluntarily removed from the market in 2010.…”
Section: The Checkered History Of Obesity Pharmacotherapymentioning
confidence: 99%